Komunikasi Pembangunan di Masjid Al Muhajirin Bumi Asri Medan Menuju Pusat Pemberdayaan Masyarakat - Fitriana Padang; Sehta Jupiter Ketaren; Alfin Qodri Hafiz; Sindy Artika; Irma Yusriani Simamora (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
In implementing an empowerment in society, paying attention to communication strategies is very important especially to realize a civilized civil society in building, interpreting and living a life. Realizing a civil society cannot be separated from the role of the community who are involved and participate in equalizing life, both through the economic, political, social and religious fields. Realizing a prosperous and prosperous society requires skills in communication and action. Through independent mosques, it is hoped that the goals of community empowerment can be carried out properly. For this reason, this study aims to determine the development communication carried out by the Al-Muhajjirin Bumi Asri Mosque to get to the center of civil society empowerment. In conducting the research, the researcher used qualitative research methods by presenting data in the form of content values, sentences and words related to the research title. In collecting data the author uses the method of observation and community service by examining the conditions around the Al-Muhajjirin Mosque and the development communication process carried out by mosque administrators on the development of independent mosques. So that researchers can draw the conclusion that there are several activities carried out by the Al-Muhajjirin mosque in an effort to empower civil society which include worship activities, recitations, da'wah in minority areas, coaching in minority areas and activities during the month of Ramadan. And the STM program carried out by the Al-Muhajjirin Mosque in an effort to develop an independent mosque